Assessment of freeze-dried Sargassum polycystum as a nutritional feed component for red tilapia (Oreochromis spp.) fingerlings - Nazarudin, Muhammad Farhan; Idrus, Ezni Suryani; Md Yasin, Ina Salwany; Azmai Amal, Mohammad Noor; Mohd Sayuti, Mohamad Azzam; Sim, Khaw Yam; Teng, Tan Hui; Ahmad, Mohd Ihsanuddin; Isha, Azizul; Aliyu-Paiko, Mohammed (Nature Research, 2025)
The effects of incorporating dried powdered Sargassum polycystum into the diet of red tilapia fingerlings (RTF) on their growth performance, nutritional composition, and serum biochemical parameters were investigated. Prior to formulation of the experimental diet and conducting the feeding trial, proton nuclear magnetic resonance and principal component analysis were used to examine the metabolic differences in S. polycystum subjected to different drying methods, (1) air-drying at room temperature, (2) freeze-drying, and (3) vacuum oven drying. Subsequently, the study explored the impact of feeding S. polycystum-based diets on the growth performance of RTF for 49 days. Results showed that RTF fed diets supplemented with 3% powdered S. polycystum exhibited higher survival rates, improved feed consumption, and enhanced efficiency compared to the control group (p < 0.05). Meanwhile, there were no significant differences (p > 0.05) observed in the content of crude fat, protein, fatty acid composition, and growth performance of RTF among all the treatment’s groups. Blood composition analysis revealed a minor elevation in serum levels of alanine aminotransferase, amylase, aspartate aminotransferase, calcium, cholesterol, total protein, and triglycerides in RTF that consumed diets enriched with seaweed, compared to the control group. Based on the results of this experiment, it may be concluded that the use of dried powdered S. polycystum as a natural supplement in feeds for RTF demonstrates potentials for better feed utilization and efficiency, and to boost growth performance of the species. Therefore, S. polycystum demonstrated potential to improve both the quality and quantity of aquaculture products.